1986
DOI: 10.1007/bf00165590
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumor protein synthesis and histological grades: A study by positron emission tomography (PET) with C11-L-Methionine

Abstract: Brain protein synthesis may be evaluated in vivo by a PET three compartment methionine model. 14 human brain tumor patients were studied. Protein synthesis rate (PSR) was increased in any glial tumor even in low grades, but this increase was statistically more important in anaplastic tumor. Radiotherapy action was evaluated in two patients. Local tumoral PSR was reduced to normal brain PSR after treatment. No difference was seen in normal cortex contralateral to the lesion between pre and post radiotherapy exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(51 citation statements)
references
References 30 publications
0
50
1
Order By: Relevance
“…This uptake does not directly reflect protein synthesis, but it represents cell avidity for amino acids. 11,12 Langen et al 28 reported that the amino acid transport system was dependent on the proliferative activity of the human glioma cells. Increased uptake of MET is present in most low-grade gliomas despite the absence of damage to the BBB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This uptake does not directly reflect protein synthesis, but it represents cell avidity for amino acids. 11,12 Langen et al 28 reported that the amino acid transport system was dependent on the proliferative activity of the human glioma cells. Increased uptake of MET is present in most low-grade gliomas despite the absence of damage to the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] In grade II glioma (DA, 33; OD, 39; OA, 17), tumor resection had a clear effect in patients with high MET uptake; however, no effect from surgery was found in the group of patients with low MET uptake. 17 Smits et al 19 analyzed DAs and oligodendrocytic tumors (OD and OA) separately in the reevaluation of the prognostic impact of the European Organisation for Research and Treatment of Cancer (EORTC) factors after adding the MET uptake as an extra prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gliomas, 11 C-MET uptake is greater in high-grade than in low-grade tumors ( Fig. 3) (27)(28)(29) and is increased in most low-grade gliomas in the absence of BBB damage-a substantial advantage over CT, conventional MRI, and 18 F-FDG PET (30,31). Therefore, 11 C-MET can provide additional information when used in combination with 18 F-FDG PET for diagnosis of these tumors.…”
Section: Petmentioning
confidence: 99%
“…Histologic and neuroradiologic features for all of the areas are shown in the Table. Discussion MET uptake by tumor tissue was first described in 1976 by Comar et al 6 Previous reports have shown that MET uptake by gliomas depends on histologic grade. 1,3,7,8 Among glial tumors, oligodendrogliomas show high MET uptake. 9 It has been suggested that oligodendroglial tumors have a high rate of cell turnover, 10 which could enhance amino acid uptake and metabolism.…”
Section: Case Reportmentioning
confidence: 99%